Cost-Effective Management of Venous Ulcer - Alam, SAN; Bashar, AHM; Alam, KM; Sabah, MN; Hossain, GMM; Hakim, ME; Badiuzzaman, M; Azad, AK (Cardiovascular Journal, 2010)
Background: Venous disorders are very common. About 20% of the population suffer from varicose veins, 2% have skin changes which may precede venous ulceration. Venous ulcers represent a common and debilitating condition associated with significant financial loss for the patients as well as the society. Treatment options for these patients are costly and time consuming. In this study we tried to find out cost-effective measures for treating this group of patients. Method: To evaluate the effectiveness and safety of superficial and perforating leg venous surgery along with pharmacotherapy 66 patients with chronic venous leg ulcers are prospectively studied. After proper history taking and clinical examination all patients underwent venous duplex ultrasonography. Patients were divided into two groups. Group I (n=30) includes patients undergoing saphenofemoral ligation and stripping of the great saphenous vein (GSV). In group II (n=36) patients underwent saphenofemoral and incompetent leg perforator ligation along with stripping of the GSV. Conservative measures, local ulcer care and pharmacotherapy were common in both groups. Result: Postoperative complications, total hospital stay and ulcer healing were studied. Ulcer healing was earlier in group II. Remarkable complications were similar in both the groups. Conclusion: For effective and economic care of venous leg ulcers, combination of standard surgical procedures including incompetent perforator and saphenofemoral ligation with great saphenous vein stripping and standard physio-pharmacotherapeutic care is essential. This combined modality of treatment is highly effective in early and complete ulcer healing in patients suffering from venous ulcers. Keywords: Venous ulcer: Saphenofemoral ligation: Perforator ligation. DOI: 10.3329/cardio.v2i2.6629 Cardiovasc. j. 2010; 2(2) : 136-141